Cellulose nanocrystals/polyaniline particles’s dispersion in polypropylene nanocomposites - BENCHIKH, Lilia (Biopolymer Applications Journal, 2024)
Sustainable development and biomass valorization are a primary means of reducing the non-renewable resources consumption and an opportunity to exploit the agricultural and forestry sectors where biomass as a renewable resource will play an important role. Cellulose is the most abundant bio-renewable material and its unique structure generates nanoparticles known as cellulose nanocrystals (CNC). Cellulose nanomaterials show a great promise for various applications therefore with a relatively low loading level, significant improvements on mechanical properties of nanocomposites could be obtained, but CNCs have a strong tendency to agglomerate and its hydrophilic characteristic leads to interfacial incompatibility with non-polar polymer matrices. In this work, polyaniline (PANI) is used as a support for Cellulose nanocrystals dispersion on Polypropylene (PP) matrix. Cellulose nanocrystals were obtained according to an experimental protocol at several stages and Polyaniline was deposited on CNC’s surface during polyaniline synthesis in CNC’s suspension. The obtained CNC/PANI nanoparticles were incorporated into the polypropylene matrix by melting compounding technique. Polypropylene nanocomposites and PANI/CNC particles were characterized with different techniques: FTIR, AFM, electrical conductivity and mechanical properties to study and assess how polyaniline and CNC affect microstructure, morphology and electrical properties of PP. Characterization technique showed that PANI was successfully synthesized on CNC’s surface and PANI/CNC material is a semiconductor. The enhanced mechanical properties of PP/PANI-CNC nanocomposites indicates a good dispersion of CNCs particles on PP matrix.